Hypertensive disorders during pregnancy and polycystic ovary syndrome are associated with child communication and social skills in a sex-specific and androgen-dependent manner - Firestein, Morgan R.; Romeo, Russell D.; Winstead, Hailey; Goldman, Danielle A.; Grobman, William A.; Haas, David M.; Parry, Samuel; Reddy, Uma M.; Silver, Robert M.; Wapner, Ronald J.; Champagne, Frances A. (Frontiers in Endocrinology, 2022)
Prenatal exposure to testosterone is implicated in the etiology of autism spectrum disorder (ASD). Hypertensive disorders of pregnancy and polycystic ovary syndrome are associated with both hyperandrogenism and increased risk for ASD. We examined whether increased maternal testosterone mediates the relationship between these hyperandrogenic disorders (HDs) during pregnancy and child communication and social skills. Maternal plasma was collected during the second trimester and parent-report measures of child communication and social skills were obtained at 4.5-6.5 years of age from 270 participants enrolled in the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-be (nuMoM2b). Our retrospective frequency-matched cohort study design identified 58 mothers with one or both of the HDs and 58 matched controls. Women diagnosed with an HD who carried a female had higher testosterone levels compared to those carrying a male (t(56) = -2.70, p = 0.01). Compared to females controls, females born to women with an HD had significantly higher scores on the Social Communication Questionnaire (t(114) = -2.82, p =0.01). Maternal testosterone partially mediated the relationship between a diagnosis of an HD and SCQ scores among females. These findings point to sex-specific associations of two HDs – hypertensive disorders of pregnancy and polycystic ovary syndrome - on child communication and social skills and a mediating effect of maternal testosterone during pregnancy. Further research is needed to understand placental-mediated effects of maternal testosterone on child brain development and neurobehavioral outcomes.